Ca[Mg3SiN4]Ce3+ phosphor: effect of particle concentration on lighting properties of the 7000K IPW-LEDs - Q. S. Vu; Tang Tin Dao; Minh Tran (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Nowadays, the white-light-emitting diodes (LEDs) have a vast application on the real-life based on its superior advantages such as energy efficiency, long lifetime, compactness, and environment-friendly and designable features in comparison with incandescent and fluorescent lamps. In this paper, we co-doping the Ca[Mg3SiN4]Ce3+ Phosphor on the phosphor compound of the 7000K In-cup Packaging White LEDs (IPW-LEDs) for improving the lighting properties. By varying the concentration of Ca[Mg3SiN4]Ce3+ Phosphor from 0% to 1.8%, the effect of the Ca[Mg3SiN4]Ce3+ Phosphor on the D-CCT, CRI, CQS, and LO of the 7000K IPW-LEDs are investigated. Using the Light Tool and software, the research results show that the concentration of the IPW-LEDs has a massive influence on the lighting properties of the 7000K IPW-LEDs. All the results are convinced by Light Tool simulation.